Enhancing Silvopastoral Resilience with Climate-Smart Practices in Tunisia's Semi-Arid Lands - Hassan, Sawsan; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2025)
This report outlines the capacity development efforts focused on silvopastoral systems in Tunisia, emphasizing the integration of climate-smart practices to enhance resilience in semi-arid regions. It highlights the benefits of using native legume species, particularly Sulla (Hedysarum coronarium), to improve soil health, livestock productivity, and biodiversity conservation. During this event, farmers received Sulla seeds to cultivate on their lands and benefited from the knowledge exchange with experienced farmers who shared practical insights on Sulla cultivation and utilization through a farmer-to-farmer approach.